The Emerald handbook of higher education in a post-covid world : new approaches and technologies for teaching and learning - Brown, Byron Alditon; Irons, Alastair, 1962- (Emerald Publishing Limited, 2022)
Teaching and learning paradigms in higher education have been called into question by the COVID-19 pandemic, requiring new approaches, technologies, and resilience. The disruption caused to higher education operations prompted many to raise questions about HEI's adaptability and readiness to handle major disasters. Focussing particularly on developing countries in Africa and the Global South, The Emerald Handbook of Higher Education in a Post-Covid World emphasizes the urgent need to reform pedagogical models and the importance of recognizing and utilizing digital learning technologies, tools, and the power of the Internet to expand the range of teaching approaches, practices and learning interaction options in an age in which information communication technology and mobile devices have become commonplace in the daily life of students, academic leaders and HE practitioners. The contributors also address the importance of supporting the individual student in learning communities where they are separated by space, and safeguarding their social and emotional wellbeing as they engage and learn through mediated-communication-systems in an era of a fundamentally changed HE environment which will not completely return to previous models. Providing perspectives from contributors across multiple nations and settings, and written in a forthright, yet engaging manner, this volume is essential reading for higher education staff, researchers, and policy makers, to ensure higher education across the world is prepared to offer the best quality teaching and learning in the Covid and Post-Covid world.